2020
DOI: 10.1111/php.13204
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response and Temperature Dependence of the Mortality of Spider Mite and Predatory Mite Eggs Caused by Daily Nighttime Ultraviolet‐B Irradiation

Abstract: The two‐spotted spider mite, Tetranychus urticae, is an economically important agricultural pest. A novel physical control method involving daily nighttime UV‐B irradiation was recently developed for use in strawberry greenhouses. However, the overlapping of leaves after March prevents direct irradiation to T. urticae on the lower leaf surface, decreasing control effect. Excessive UV‐B irradiation causes leaf sunscald in winter. Therefore, optimization of UV‐B irradiance and a compensatory control agent are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
1
14
0
1
Order By: Relevance
“…In a previous study, egg hatchability under intermittent nighttime UV-B irradiation simulating the UV method drastically increased from 23.3% to 97.0% in T. urticae (0.0972 kJ m −2 day −1 ) and from 20.1% to 89.0% in N. californicus (0.27 kJ m −2 day −1 ), as temperature increased from 18 to 30°C. 8 However, in Method-1, the hatchability and photoreactivation efficiency in both T. urticae and N. californicus eggs decreased slightly, or did not change, after a single dose of UV-B irradiation exposure as temperature increased, except for N. californicus at 0.288 kJ m −2 . In that study, the hatchability of N. californicus eggs was positively correlated with temperature increase, regardless of Vis irradiation after UV-B irradiation; this positive correlation was likely caused by factors other than PER enhancement by temperature.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In a previous study, egg hatchability under intermittent nighttime UV-B irradiation simulating the UV method drastically increased from 23.3% to 97.0% in T. urticae (0.0972 kJ m −2 day −1 ) and from 20.1% to 89.0% in N. californicus (0.27 kJ m −2 day −1 ), as temperature increased from 18 to 30°C. 8 However, in Method-1, the hatchability and photoreactivation efficiency in both T. urticae and N. californicus eggs decreased slightly, or did not change, after a single dose of UV-B irradiation exposure as temperature increased, except for N. californicus at 0.288 kJ m −2 . In that study, the hatchability of N. californicus eggs was positively correlated with temperature increase, regardless of Vis irradiation after UV-B irradiation; this positive correlation was likely caused by factors other than PER enhancement by temperature.…”
Section: Discussionmentioning
confidence: 92%
“…UV-B and Vis irradiation were administered using a UV-B lamp (6 W; Panasonic Co. Life Solution) and two halogen lamps (130 W; JDR110V-85WHM/K7-H; Ushio Lighting; separated by 22.5 cm), respectively, affixed to a shelf positioned at a height of 67 cm in a growth chamber, as described previously. 8,13,15,22 The growth chamber was illuminated with fluorescent lights (approximately 7000 lx) from 8:00 AM to 22:00 PM (14:10 h light/dark); the fluorescent lights were turned off as necessary for the experiment. UV-B irradiation from the UV-B lamp peaked at 310 nm (Figure S1), and its intensity was 0.16 W m −2 .…”
Section: Uv-b and Vis Irradiation Device And The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As leaves grow and produce shade, spider mite survival may increase, especially in densely planted commercial greenhouses. Laboratory experiments have also revealed that rising temperatures decrease the mortality of spider mites on UV‐B irradiation 14 . These findings imply that the effect of the UV method on spider mites is dampened by biological and environmental factors in spring.…”
Section: Introductionmentioning
confidence: 92%
“…Although N. californicus eggs are more vulnerable to a single acute dose of UV‐B irradiation than are T. urticae eggs, 18 UV‐B vulnerability is reversed under the UV method. N. californicus eggs are more resistant to UV‐B radiation than T. urticae eggs 14,19 . Eggs are the development stage most sensitive to UV‐B irradiation 20,21 .…”
Section: Introductionmentioning
confidence: 99%